The Specific Role of Verb â€œTo Carryâ€ in Balinese - Ida Ayu Pristina Pidada; Mirsa Umiyati; Ni Wayan Kasni (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2019)
A number of studies on verbs as one of the linguistic grammatical categories, serving to desccribe events, have been to explore in depth their more distinct types according to their semantic primitives under the natural semantic metalanguage theory approach. This research aims is to features the semantic types and specific roles of the verb ‘to carry’ in Balinese from the natural semantic metalanguage theory perspective. This study is a qualitative study. The semantic types of the verb in question was first classified in order to ease the identification of their specific semantic roles. The results of research show type of semantic roles were restricted to agent for the arguments serving as an actor of the activity described with the each of semantic type of the verb ‘to carry’ and patient for those serving as target of the said activity. This research discloses a 21 type of Balinese verbs which semantically have an intimate relation to the verb ‘to carry’; they are nèngtèng, ningting, nyangkol, nyangkil, nyuun, negen, ngandong, nenggolong, nyelet, nyelepit, ngabin, nampa, ngundit, nangal, nandan, nyekel, nikul, ngenyang, mundut, nyunggi, dan ngayot.